Uterine Tumors Resembling Ovarian Sex Cord Tumors in Four Baboons (Papio spp.). Issue 5 (September 2018) - Mangosing, Sara; Perminov, Ekaterina; Gonzalez, Olga; Barkei, Erica K.; Corbin, Emily M.; Kumar, Shyamesh; Dick, Edward J.
Uterine tumors resembling ovarian sex cord tumors (UTROSCTs) are rare uterine neoplasms that exhibit prominent sex cord-like differentiation. The authors describe 4 cases of UTROSCTs that were identified as incidental lesions in female baboons. All baboons were in good body condition. One animal had a 2-mm-diameter yellow-tan mass in the uterine body along the attachment of the left broad ligament; the other 3 did not have any gross lesions in the uterus. Histologically, the myometrium contained multifocal well-demarcated neoplasms composed of cuboidal to columnar cells arranged in variable arrangements of sheets, nests, cords, trabecular, and retiform patterns that occasionally formed Call-Exner-like bodies. In all cases, the neoplastic cells were diffusely positive for WT-1 and negative for calretinin, CD99, and desmin. One case was positive for inhibin and CD10. To the best of the authors' knowledge, this is the first report of UTROSCTs in nonhuman primates and in the veterinary literature.